The Combination of Red and Blue Light, Radiofrequency and Intense Pulsed Light for the Treatment of Facial Postacne Erythema [Letter] - Zhang JY; Xu BH (Dove Medical Press, 2022)
Jia-Yu Zhang, Bao-Hua Xu China-Japan Friendship Hospital (Institute of Clinical Medical Sciences), Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Bao-Hua Xu, Chinese Academy of Medical Sciences & Peking Union Medical College, China-Japan Friendship Hospital, 2 Cherry Blossom Garden East Street, Chaoyang District, Beijing, 100029, People’s Republic of China, Email drbaohuaxu@163.com